2004
DOI: 10.1002/jcp.10472
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic lymphoma kinase proteins in growth control and cancer

Abstract: The normal functions of full-length anaplastic lymphoma kinase (ALK) remain to be completely elucidated. Although considered to be important in neural development, recent studies in Drosophila also highlight a role for ALK in gut muscle differentiation. Indeed, the Drosophila model offers a future arena for the study of ALK, its ligands and signalling cascades. The discovery of activated fusion forms of the ALK tyrosine kinase in anaplastic large cell lymphoma (ALCL) has dramatically improved our understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
185
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(193 citation statements)
references
References 298 publications
4
185
0
4
Order By: Relevance
“…In samples from patients with Paget's disease of the breast, ALK is expressed in very high levels in the cytoplasm and in nuclei of stromal fibroblasts and in the inflammatory cells, whereas in the epithelial cells ALK is localized in the cytoplasm ( Figure 2H). These extraordinary differences in the patterns of expression of ALK in breast cancer has been previously described in studies of the different ALK fusion oncogenic proteins that characteristically are observed in ALCLs [24] and differ very significantly from normal breast tissues.…”
Section: Resultsmentioning
confidence: 51%
“…In samples from patients with Paget's disease of the breast, ALK is expressed in very high levels in the cytoplasm and in nuclei of stromal fibroblasts and in the inflammatory cells, whereas in the epithelial cells ALK is localized in the cytoplasm ( Figure 2H). These extraordinary differences in the patterns of expression of ALK in breast cancer has been previously described in studies of the different ALK fusion oncogenic proteins that characteristically are observed in ALCLs [24] and differ very significantly from normal breast tissues.…”
Section: Resultsmentioning
confidence: 51%
“…Translocations linking ALK to multiple fusion partners were subsequently identified in ALCL as well as in other malignancies, including neuroblastomas and myofibroblastic tumors (11). A novel gene fusion of ALK and the echinoderm microtubule-associated protein-like 4 (EML4) was recently identified in non-small cell lung cancer (NSCLC; ref.…”
Section: Introductionmentioning
confidence: 99%
“…A discrete subset of ALCLs is characterized by specific chromosome translocations, in which the anaplastic lymphoma kinase (ALK) gene, on chromosome 2, is fused to several partners, most frequently to the nucleophosmin (NPM) gene (2,3). The presence of ALK fusions in inflammatory myofibroblastic tumors as well as lymphoma implies that ALK is involved in oncogenesis of both nonhematopoietic and hematopoietic tumors (4). Moreover, the deregulated expression of the ALK receptor has been documented in a subset of nonlymphoid tumors, including sarcomas, neuroblastomas, and gliomas (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise mechanisms by which NPM-ALK mediates cellular transformation and its requirements for tumor growth and survival are still unclear. Activated ALK chimeras bind multiple adaptor proteins capable of firing different pathways regulating cell proliferation, survival, and transformation (4,13,14). The known adaptors include Grb2, Shc, IRS-1, phospholipase CĪ³ (PLC-Ī³) PI3K, and Jak3, which activate numerous downstream molecules, including cyclin D, ERK1/2, STAT, and AKT (3,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%